Official Secrets Act: a commentary / Mohd Ramli Othman - Othman, Mohd Ramli (Faculty of Law, 1987)
The Official Secret s Act 1972 (Revised 1986) is modelled on the Official Secrets Act 1911 of England. The English Act, an anti espionage legacy of pre World War 1, was enacted in the wake of hysteria leading up to the outbreak of the war. Never in the history of Malaysia has a Bill generated as much interest, debate and controversy as the Official Secrets (Amendment) Bill 1986. The OSA crisis had attracted much attention and criticism from the general public, especially the political parties. The OSA 1972 received the Royal Assent on 26th Sept. 1972 and was subsequently published in the Gazette on 30th Sept 1972. It its original form, the Act was first amended in 1983. A second amendment followed in March 1986 and subsequently the third in October 1986, culminating into the most controversial piece of legislation ever proposed by the Government since Independence in 1957...